Accuracy of ankle and knee angle measurements with thin flex sensors - Schindelwig, K. N.; Marterer, D.; Morawetz, S.; Kapferer, R.; Csapo, W. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The accurate determination of joint angles is an important tool for biomechanical research. Electronical goniometers are cheap and easy to use but, in some situations, their application is complicated. For instance, in alpine skiing, the thickness of goniometers precludes mounting within ski boots, impeding the reliable acquisition of ankle joint angles. Externally fixed goniometers are also prone to damage, e.g. through impacts with external objects such as flex poles. Flex sensors feature a thickness of 0.4 mm only and may, therefore, represent an alternative when the use of conventional goniometers is not feasible. The aim of this study was to determine the accuracy of knee and ankle joint angles as measured by flex sensors during deep squats. Methods: Three subjects (age 21.3 ± 1.6 yrs, height 1.72 ± .09 m, mass 68.1 ± 3.1 kg) performed 6×15 repetitions of deep squats. After completion of 2 series, movement speed was gradually increased from 15-45 repetitions per minute. Movement speed was controlled through the use of an electronic metronome. The 11.4 cm long flex sensors (Spectra Symbol, SEN-08606, Salt Lake City, UT) were attached on both legs, across (i) the tibiotalar joint (from the navicular bone to the distal end of the tibia) and (ii) the knee joint (along the popliteal fossa). The attachment sites were chosen to allow longitudinal motion of the sensors. Data were sampled at 1500 Hz and transmitted wirelessly to a recording system (Telemyo 2400T G2, Noraxon, USA). Reference measures were acquired with an active three camera motion capturing system sampling at 100 Hz (AS 200, LUKOtronic, Austria). Optical data of the right and left leg were separately recorded and manually synchronized with the flex sensor recordings. The maximum and standard deviation (SD) of differences between the data obtained with both systems were calculated as measure of accuracy of the flex sensors. Results: Across the six deep squat series, the mean ranges of movement in ankle and knee joint were 39° and 94°, respectively. For the ankle and knee joint, the mean of the maximum differences between the measures obtained by flex sensors and motion analysis were 9.1° (23.6%) and 13.1° (14.0%), respectively. The mean of the SDs of differences were 2.9° (7.5%) and 4.0° (4.3%). Measurement accuracy was independent of movement speed. Discussion: The flex sensors yielded a satisfactory accuracy for measurements of ankle and knee angles. Therefore, they may be used as low-cost system for angle measurements that may be applied where usage of electronic goniometers is not feasible due to space constraints or risk of damage. However, it should be noted that conventional goniometers feature superior accuracy and should be used when high measurement precision is required.